ISSUES OF FAMILY BUSINESS DEVELOPMENT USING ALTERNATIVE ENERGY SOURCES (ResearchJet Journal of Analysis and Inventions, 2021)
This article provides ideas and feedback on the development of family businesses using alternative energy sources.